Prevalence of Salmonella contamination in pig and pork at farms and slaughterhouses in the northern provinces of Vietnam - Pham Thi Ngoc; Nguyen Tien Thanh; Tran Thi Hanh; Hung Nguyen-Viet (2013)
Salmonella is known as one of the most frequent foodborne zoonoses in the world and has been isolated from humans and pork products. The aim of this study was to assess the prevalence of Salmonella in the pig farms and during slaughter through practice analysis, serotyping, and focusing on the role of specific practices in the final carcass contamination. 82 Salmonella isolates were found among anal swabs, barn floor swabs, feed, drinking water, wastewater, and breeding equipment samples in pig farms and in the same type of samples and carcass swabs collected at slaughterhouses, In total, the main serovars were Salmonella enterica subsp. entericaserovar (S.) Derby (25.6%), S. Typhimurium (23.2%) and S.Rissen (13.4%). Other serovars including S. Anatum, S. Braenderup, S.Chartres, and S. Meleagridis appeared from 2.4% to 6.1%. Isolating and serotyping showed that live pigs’ faeces, probably through unloading, lairage or offal preparation, were the principal source of Salmonella contamination of the slaughter environment and carcasses. However, we could not establish a direct link between the environment and carcasses. Similarly, the direct contamination of carcasses through faecal material from the same pig was not clear. Thus, our results suggest that the main source of carcass contamination was indirect, through the environment, since the pigs are slaughtered on the ground. A direct contamination was observed probably through defective practices and the lack of wastewater management. Control measures could largely decrease the carcass contamination rate. Particular attention should be paid to the contact of the carcass with the ground or workers, especially after scalding, to improved separation between soiled and clean areas, to wastewater management and to the cleaning and disinfection protocol.